الغش في الامتحانات المدرسية ـ دراسة تحليلية بَعْدية لمجموعة من الدراسات في المفاهيم والإجراءات المنهجية والنتائج - معمرية, بشير (جامعة الوادي - University of Eloued, 2018)
أجري البحث على ظاهرة الغش في الامتحانات المدرسية بأسلوب التحليلي الَبْعدي، وتنا 42دراسة ميدانية، أجريت كلها في البلدان العربية وتناول التحليل كلا من المفاهيم التي استعملت لوصف ظاهرو الغش، والإجراءات المنهجية التي اتبعت في إجراءات البحوث، والنتائج التي تم التوصل إليها The study was conducted on the phenomenon of cheating in the school exams in the post-analytical method. It dealt with 24 field studies, all of which were conducted in the Arab countries. The analysis dealt with both the concepts used to describe the phenomenon of cheating, the methodological procedures followed in the research procedures and the results reached
Cheating in the School Exams Analytical study of the dimension of the group Of studies in concepts, methodological procedures and results
مقال في مجلة السراج في التربية وقضايا المجتمع بجامعة الوادي
Keywords: الغش، الامتحانات المدرسية; the phenomenon of cheating , school exams